The Work System of The Election Commission With The Group of Voting Operators Based on Law Number 7 Of 2017 in The 2019 Convenient General Elections First Perspective of Siyasah Dusturiyah - Handayati, Sadewi; Fitri, Hidayati; Efendi, Roni (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
The research focus is to examine the Work System of the General Election Commission (KPU) with the Voting Organizing Group (KPPS) in determining the Permanent Voters List (DPT) in the 2019 simultaneous General Election (Election). There are three research questions in this study, they are: (1) how the General Election Commission work system with Voting Organizers Group Based on Law No.7 / 2017 in Determining the Final Voters List at the 2019 Concurrent General Election, (2) How is the fiqh siyasah dusturiyah review of the work system of the General Election Commission and the Voting Organizing Group in determining the Final Voters List at the 2019 simultaneous general election?.  The object of this study  uses a type of normative legal research or library research with a qualitative typology, namely the search results from the literature material are analyzed and described comprehensively in relation to the work system of the KPU and KPPS on the DPT determination in the 2019 simultaneous election in the perspective of fiqh siyasah dusturiyah. The result of these research are: The work systems of the KPU and KPPS did not disharmony in determining the DPT in the 2019 Concurrent Elections, because the KPPS 'authority was limited to announce and post the DPT. The inaccuracy of the DPT for the 2019 Concurrent Election is due to the disharmony of the work system in determining the DPT in the 2019 simultaneous elections that occur within the KPU organization itself, namely between the Central KPU, Provincial KPU, and Regency / City KPU. Furthermore, in determining the DPT in the 2019 simultaneous election, the perspective of fiqh siyasah dusturiyah can guide the values of deliberation as regulated in the Islamic State Administrative Law, so that there is no disharmony in the determination of the DPT. The disharmony occurred because the KPU, both the Central KPU, Provincial KPU, and Regency / Municipal KPU, did not follow the principle of deliberation in determining the DPT in the 2019 simultaneous elections